Spiritual well-being mediates between psychological capital and emotional experiences: evidence from college students at a private residential university in India - Jerin V Philipose; Rajneesh Choubisa; Akash Dubey (Discover Mental Health)
Abstract College students worldwide are encountering significant mental health challenges and positive psychological approaches are effective in addressing these issues. Psychological capital as a construct having origin from organizational psychology plays an important role in young people’s education and mental health. The dimensions of psychological capital and spiritual well-being play an important role in manifesting emotional experiences, both positive and negative, among young individuals. In the contemporary scenario, where social and economic factors act as deciding factors in deciphering and influencing emotions, there is a dire need to focus on the positive developmental aspects of human behavior. We, thus, explore the interconnection between psychological capital and spiritual well-being and quantitatively investigate how both of them influence the emotional experiences of college students (N = 214). Results from the regression analysis suggest that psychological capital predicts positive emotions, whereas spiritual well-being mediates this relationship. One of the practical implications of our results suggest that these three variables have good interventional potential for well-being promotion studies.